Digitalization, Innovation, and Financial Inclusion Among Leap Beneficiaries: The Case of Ada East District and La Nkwantanang Madina Municipal - Normegbor, D. K. (University of Ghana, 2025)
The availability and use of financial services and products by all segments of the population is fundamental to global development. Nonetheless, more than two billion people globally said they lacked a formal bank account. Particularly for the underprivileged and marginalized, digital finance presents an opportunity to lower costs and provide access to a broad range of financial services. However, the lack of access to computers, smartphones, or the internet for financial transactions may result in even greater financial exclusion. Vulnerable groups and demographics, such as the elderly, the impoverished, and those living in rural areas, are further excluded due to the differences in access and use of these ICT tools. Hence, widens the disparity in financial inclusion. This study examines the impact of the digital divide on the adoption of digital financial services among a vulnerable group like the LEAP (Livelihood Empowerment Against Poverty) beneficiaries and explores measures government can take to mitigate the risk of a digital financial divide. Using a qualitative research approach, the study collected data through a semi-structured interview from respondents in the Ada East District and La Nkwantanang Madina Municipal. The study found that the digital divide significantly undermines the adoption of digital financial services among LEAP beneficiaries leaving them as passive users as they lack the enabling environment to engage with digital finance. The findings also suggested that the persistence of the challenges reflect not only resource and infrastructure constraints but also policy, lack of financial training and service design failures that continue to hinder adoption. The study concludes by recommending infrastructure development, digital literacy and capacity building, device accessibility and policy coordination as best way to promote the adoption of digital financial services among LEAP beneficiaries.
MPhil. Political Science
Keywords: financial services; development; ICT tools